The online for offline mobile retail business strategy: sustainable multichannel services. (15th December 2022) - Sohn, Kwonsang; Sung, Christine; Zhang, Qingxuan; Kwon, Ohbyung
Online for offline (O4O) e-commerce is a new multichannel strategy that is being adopted worldwide, whereby successful online companies launch offline retail stores. Despite this new retail trend, it is unclear whether this new business model is sustainable. Therefore, the purpose of this empirical study is to identify factors affecting consumers' intention to continue using online and offline channels established by successful online brands using an O4O strategy, and to test the halo effect of online stores going offline. The findings of this study confirm that utilitarian value, hedonic value, and parasocial relationships have significant effects on intention to continue visiting online and offline stores. Also, consumers' intention to continue to visit online stores strongly influences the perceived utilitarian and perceived hedonic value of the offline store. These results suggest that the perceived utilitarian and hedonic value of the online store can expand and sustain enterprises adopting the multichannel strategy.